Thermal-mechanical evolution behaviors of metal matrix diamond composite by powder bed fusion-laser beam - Yingbo Peng; Taitong Jin; Boyue Yang; Yasong Shi; Yuan Gao; Wei Zhang (Journal of Materials Research and Technology, 2024)
The thermal damage of diamond and the residual stress have always been the critical issues to be resolved in the development of metal matrix diamond composites. In the presented study, FeCoCrNi high entropy alloys (HEAs)-diamond composites were fabricated by powder bed fusion-laser beam of metals (PBF-LB/M), using un-coated diamond and Ti–Ni coated diamond, respectively. Based on the numerical and experimental analysis, the effect of thermal-mechanical behavior on the microstructures and mechanical properties of the composites was systematically investigated. By establishing the temperature field of the PBF-LB molten pool, the defects, diamond graphitization and in-situ TiC formation were studied. The start-temperature for diamond graphitization in coated samples was 365 °C higher than that of un-coated samples, due to the diffusion barrier effect of TiC. Subsequently, by thermo-mechanical coupling, the property and value of the residual stress exhibited sudden change at the diamond/matrix interface. The TiC intermediate layer significantly relieved the stress concentration at interface, and effectively avoided cleavage fracture of the diamond and the initiation of interfacial cracks. At the moderate molten-pool temperature, the coated diamond composites exhibited optimal performance, as bending strength of 913 MPa, friction coefficient of 0.25 and worn mass loss of 0.67 mg. Finally, the quantitative relationship between PBF-LB molten-pool temperature and the relative density, graphitization degree, residual stress, retention(bending strength) and wear performance was established, to demonstrate the thermal-mechanical evolution of the HEAs-diamond composites by PBF-LB.